FACTOR FOR CORRECTING THE RAINFALL OF CHIRPS SATELLITE DATA AGAINST OBSERVATION DATA ON THE CILIWUNG WATERSHED(CASE STUDY OF KEMAYORAN METEOROLOGI STATION) - Endah Kurniyaningrum; Mutiara Difa Faluty; Hegi Daniel Mulya; Sih Andayani; Dina Paramitha Anggraeni Hidayat; Wahyu Sejati; Hira Sattar (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2024)
The hydrological and environmental cycles in a river area strongly affect rainfall intensity and seasonal patterns. To accurately assess water resource capacity, precise rainfall data from each observation station is crucial. However, unevenly distributed rain gauges often challenge researchers, as insufficient data can hinder their analysis. In these situations, satellite images can provide valuable additional information.Aims: The objective of this study was to analyze the accuracy of CHIRPS satellite rainfall data from observation stations in the Ciliwung watershed, especially in the DKI Jakarta Province area, over the last 30 years (1993–2022).Methodology and results: Statistical analysis such as multiple linear regression with the stepwise method is used to analyze CHIRPS rainfall against observed rainfall data according to the location of the rain station. The validation results in this study show that the average results of the two observation stations have a value of R2 = 0.91 and NSE = 0.9068.Conclusion, significance and impact study: CHIRPS data can be categorized as very good if used as an alternative to limited observational rainfall data, which can then be used in analyzing water availability in the Ciliwung watershed (Jakarta).